PJMHS 2022
DOI: 10.53350/pjmhs22162986
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Appendix Perforation in Patients Presenting with Acute Appendicitis: A Cross-Sectional Study

Abstract: Aim: To find out the frequency of perforated appendix among patients presenting with acute appendicitis. Study design: A cross-sectional study Place and Duration: This study was conducted at Sindh Employee Social Security Hospital Landhi Karachi, Pakistan from July 2020 to November 2021. Methodology: This study includes 205 patients. All the details like age, gender, and previous history associated with diabetes and fasting blood sugar were noted. The surgeries were performed by a single surgeon who detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The complete preoperative diagnosis of PAp is of significant clinical importance as its management differs from that of uncomplicated appendicitis [5] . While patients that had surgery for uncomplicated appendicitis tend to attain quick recovery, usually within one or two days post-op, with limited chances of complications, particularly after having a laparoscopic appendectomy, some studies have shown that most PAp patients will 3/6 https://www.doi.org/10.53964/jmmi.2023001 have longer hospital stay and increased possibility of post-op complications [6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete preoperative diagnosis of PAp is of significant clinical importance as its management differs from that of uncomplicated appendicitis [5] . While patients that had surgery for uncomplicated appendicitis tend to attain quick recovery, usually within one or two days post-op, with limited chances of complications, particularly after having a laparoscopic appendectomy, some studies have shown that most PAp patients will 3/6 https://www.doi.org/10.53964/jmmi.2023001 have longer hospital stay and increased possibility of post-op complications [6] .…”
Section: Discussionmentioning
confidence: 99%
“…While uncomplicated appendicitis can sometimes be treated using antibiotic therapy since the wall of the appendix is not compromised, complicated appendicitis on the other hand requires immediate surgical intervention [4] . When the wall of the inflamed appendix gets compromised, this leads to perforation, abscess, and peritonitis, which if left unmanaged can cause sepsis and potentially death [5] . This case report aims to present some of the ultrasound appearances seen in perforated appendicitis (PAp) and to review some of the relevant literature available on the imaging of PAp and its accompanying complications.…”
Section: Introductionmentioning
confidence: 99%